2016
DOI: 10.1371/journal.pntd.0004149
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Efficacy and Safety of Ciclosporin to Prednisolone in the Treatment of Erythema Nodosum Leprosum: Two Randomised, Double Blind, Controlled Pilot Studies in Ethiopia

Abstract: BackgroundErythema Nodosum Leprosum (ENL) is a serious complication of leprosy. It is normally treated with high dose steroids, but its recurrent nature leads to prolonged steroid usage and associated side effects. There is little evidence on the efficacy of alternative treatments for ENL, especially for patients who have become steroid resistant or have steroid side effects. These two pilot studies compare the efficacy and side effect profile of ciclosporin plus prednisolone against prednisolone alone in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 19 publications
0
12
0
1
Order By: Relevance
“…Data from eight studies were included in the final meta-analysis. One of the publications [ 27 ] included two pilot trials, which are represented separately in the analysis. Fig 2 provides an overview of the overall disability weights for the Grade 2, Grade 1, and Grade 0 disability from the univariate meta-analysis model, for ease of presentation.…”
Section: Resultsmentioning
confidence: 99%
“…Data from eight studies were included in the final meta-analysis. One of the publications [ 27 ] included two pilot trials, which are represented separately in the analysis. Fig 2 provides an overview of the overall disability weights for the Grade 2, Grade 1, and Grade 0 disability from the univariate meta-analysis model, for ease of presentation.…”
Section: Resultsmentioning
confidence: 99%
“…In a study in Ethiopia of 33 participants with ENL, 57% reported GI AEs. 20 An Indian RCT reported 43% of participants experienced GI AEs. 18 ENL is a chronic condition, therefore many study trial participants have a long history of corticosteroid use.…”
Section: Methods and Analysismentioning
confidence: 99%
“…14 Since the introduction of MDT, there have been eight randomised controlled trials (RCTs) of potential treatments for ENL, involving just 369 (median 22 (range 10-100)) individuals and all had significant methodological limitations including lack of standardisation, allocation concealment and non-validated outcome measures. [15][16][17][18][19][20][21][22] Rationale for using methotrexate Methotrexate (MTX) is an immunosuppressant agent used in the treatment of malignant and inflammatory diseases. 23 24 MTX was first introduced in 1948 to treat acute leukaemia and in 1951, Gubner published his findings on the rapid improvement of psoriasis in patients being treated with aminopterin, an unstable precursor of MTX.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on giving high dose methylprednisolone did not show an improvement in nerve damage when used to treat reactions and they required additional prednisolone [82]. Also addition of steroid sparing agents like cyclosporin to steroid treatment did not improve nerve damage outcomes in ENL [83].…”
Section: Treatment Of Lepra Reactionsmentioning
confidence: 99%